Traditional Games: techniques in group guidance for Strengthening Pancasila student profiles in elementary schools - Smith, Mardia Bin; Sari, Permata; Tuasikal, Jumadi Mori Salam (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2023)
Strengthening the Pancasila student profile is the latest issue in the world of education in Indonesia. All projects and learning methods used aim to shape the character of Pancasila students. This study aims to determine the effectiveness of group guidance using the traditional bilu-bilu game to strengthen the profile of students of Pancasila at SD N 60 Kota Timur. This research is a single case experimental design study with A-B design and involves four respondents using a random sampling method. The instruments used in this study were the Pancasila student profile scale and observation guidelines. The analysis technique used is clinical and statistical analysis. The results showed that there was a significant increase in the profile of Pancasila students through traditional bilu-bilulu games at baseline A1, intervention, and baseline A2. Schools can adapt classic games in guidance and counselling services or in the learning process to strengthen the Pancasila student profile. This study combines group guidance stages with traditional games, allowing students to gain meaningful experiences in each guidance session. The results of this study can be used as a reference for schools to develop group guidance service programs using local wisdom.